2018
DOI: 10.1136/bmjoq-2017-000295
|View full text |Cite
|
Sign up to set email alerts
|

Improving wait time from referral to opiate replacement therapy in a drug recovery service

Abstract: While the reported incidence of heroin use in the UK has reduced, related hospital admissions and associated mortality have continued to increase. Prompt access to treatment (opiate replacement therapy (ORT) and counselling support) have been shown to reduce risk and offer clients the optimal route to recovery. The Specialist Drug and Alcohol Recovery Service (Osprey House) within National Health Service Highland had lengthy delays from referral to commencing ORT (median wait 56 days), which this project aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Unfortunately, there can be extremely long wait times from patient referral to treatment, which can lead to high disengagement rates (up to 75-80%) by individuals with SUD. Beattie et al (60) found average referral wait times of 56 days; the National Council for Behavioral Health (61), which examined 200 sites in Minnesota, Pennsylvania, and Washington, found a similar wait time of approximately 50 days from the service user's first call to the first service appointment. Barriers in the referral process include difficulties in determining patient eligibility, lack of transparency regarding treatment capacity, referral source knowledge/understanding of options, and issues with communication between referral source and recipient (62).…”
Section: Providing Treatmentmentioning
confidence: 99%
“…Unfortunately, there can be extremely long wait times from patient referral to treatment, which can lead to high disengagement rates (up to 75-80%) by individuals with SUD. Beattie et al (60) found average referral wait times of 56 days; the National Council for Behavioral Health (61), which examined 200 sites in Minnesota, Pennsylvania, and Washington, found a similar wait time of approximately 50 days from the service user's first call to the first service appointment. Barriers in the referral process include difficulties in determining patient eligibility, lack of transparency regarding treatment capacity, referral source knowledge/understanding of options, and issues with communication between referral source and recipient (62).…”
Section: Providing Treatmentmentioning
confidence: 99%
“…Demands for substance abuse treatment have been increasing much faster than capacities. Average delays have been found to range from more than 2 months to more than a year…”
Section: Sources Of Delaysmentioning
confidence: 99%